Deposition of exchange-coupled dinickel complexes on gold substrates utilizing ambidentate mercapto-carboxylato ligands - Börner, Martin; Blömer, Laura; Kischel, Marcus; Richter, Peter; Salvan, Georgeta; Zahn, Dietrich R. T.; Siles, Pablo F.; Fuentes, Maria E. N.; Bufon, Carlos C. B.; Grimm, Daniel; Schmidt, Oliver G.; Breite, Daniel; et al. (Beilstein Journal of Nanotechnology, 2017)
The chemisorption of magnetically bistable transition metal complexes on planar surfaces has recently attracted increased scientific interest due to its potential application in various fields, including molecular spintronics. In this work, the synthesis of mixed-ligand complexes of the type [NiII2L(L’)](ClO4), where L represents a 24-membered macrocyclic hexaazadithiophenolate ligand and L’ is a ω-mercapto-carboxylato ligand (L’ = HS(CH2)5CO2− (6), HS(CH2)10CO2− (7), or HS(C6H4)2CO2− (8)), and their ability to adsorb on gold surfaces is reported. Besides elemental analysis, IR spectroscopy, electrospray ionization mass spectrometry (ESIMS), UV–vis spectroscopy, and X-ray crystallography (for 6 and 7), the compounds were also studied by temperature-dependent magnetic susceptibility measurements (for 7 and 8) and (broken symmetry) density functional theory (DFT) calculations. An S = 2 ground state is demonstrated by temperature-dependent susceptibility and magnetization measurements, achieved by ferromagnetic coupling between the spins of the Ni(II) ions in 7 (J = +22.3 cm−1) and 8 (J = +20.8 cm−1; H = −2JS1S2). The reactivity of complexes 6–8 is reminiscent of that of pure thiolato ligands, which readily chemisorb on Au surfaces as verified by contact angle, atomic force microscopy (AFM) and spectroscopic ellipsometry measurements. The large [Ni2L] tail groups, however, prevent the packing and self-assembly of the hydrocarbon chains. The smaller film thickness of 7 is attributed to the specific coordination mode of the coligand. Results of preliminary transport measurements utilizing rolled-up devices are also reported.
Keywords: ambidentate ligands; chemisorption; gold surfaces; macrocyclic complexes; mercapto-alkanecarboxylic acid